2015
DOI: 10.1017/s1474746415000020
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Start: The Use of Welfare Food Vouchers by Low-Income Parents in England

Abstract: The Healthy Start scheme provides food welfare to pregnant women and children under four years old in the UK. The Government provides vouchers to families living on a low income that can be exchanged for infant formula, plain cow's milk and fresh or frozen fruit and vegetables. This article reports on a qualitative study of parents using Healthy Start in England. Interviews were conducted with 107 parents from thirteen areas in England. Most found the scheme easy to use, but some vulnerable groups were unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 21 publications
(23 reference statements)
0
38
0
Order By: Relevance
“…Fifty full-text articles were excluded based on the assessment of relevance (n=33) or because they were not primary studies (n=15) or the findings were duplicated (n=2). Therefore, 38 primary studies were included in this review: four UK studies on Healthy Start 6 7 15 16 and 34 US studies on WIC 17–50 (see online PRISMA Flow Diagram and online supplementary file 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty full-text articles were excluded based on the assessment of relevance (n=33) or because they were not primary studies (n=15) or the findings were duplicated (n=2). Therefore, 38 primary studies were included in this review: four UK studies on Healthy Start 6 7 15 16 and 34 US studies on WIC 17–50 (see online PRISMA Flow Diagram and online supplementary file 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies reported women’s nutritional outcomes: three studies on Healthy Start and 22 studies on WIC. The Healthy Start studies reported perceived outcomes only; some women said they consumed more cow’s milk, fruits and vegetables after receiving Healthy Start vouchers, 6 7 16 whereas other women said the vouchers ‘freed up money to do other things’ and ‘helped them to manage better financially’ (p 59). 7 The WIC studies were published between 1981 and 2015, but the most useful data was extracted from two studies comparing women’s diets before and after the 2009 WIC revisions when the ‘cash value vouchers’ for fruits and vegetables were introduced (there was no allowance for fresh fruits and vegetables before 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, it has been demonstrated that people may compartmentalise spending, mentally allocating some income to specific products, even where there are no restrictions on elements of income 27. Some HS participants reported that the vouchers acted as a reminder of the importance of a healthy diet, and that they bought less F&V once they stopped receiving vouchers 28. In addition, participants reported that the vouchers enabled them to buy a wider range and quality of vegetables, something that may not result in a measurable increase in quantity of F&V consumed but is arguably a positive outcome 10 28.…”
Section: Discussionmentioning
confidence: 99%